2012
DOI: 10.21273/hortsci.47.9.1338
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination and Early Seedling Growth of Cynanchum bungei Decne (Asclepiadaceae) in Response to Photoperiod, Temperature, and Seed Size

Abstract: Cynanchum bungei Decne is a rare, endemic, and important medicinal plant species in China. Seed germination and early seedling growth of large seeds (greater than 7 mm) and small seeds (smaller than 7 mm) were investigated at three temperatures (15, 20, and 25 °C) in both continuous light and alternating light/dark photoperiods to determine seed propagation requirements. Photoperiod significantly affected seed germination and early seedling growth. Germination and seedling gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…At the end of the 13-day experimental runs, the final percent germination and germination vigor was greatest at 0-and 16-h light exposure and lowest at 24-h light exposure (Table 1). While our results agree with Roberts (1973), they conflict with the benefits of light on germination percentage and germination vigor of four other Rhododendron species that require light for germination (Zhang, 2012).…”
Section: Effect Of Different Light Time On Germination Of Rhododendrosupporting
confidence: 69%
See 1 more Smart Citation
“…At the end of the 13-day experimental runs, the final percent germination and germination vigor was greatest at 0-and 16-h light exposure and lowest at 24-h light exposure (Table 1). While our results agree with Roberts (1973), they conflict with the benefits of light on germination percentage and germination vigor of four other Rhododendron species that require light for germination (Zhang, 2012).…”
Section: Effect Of Different Light Time On Germination Of Rhododendrosupporting
confidence: 69%
“…The results showed that there was little difference among the effects of the three temperature on the starting germination time and germination speed. While seed germination of Cynanchum bungei (Zhang, 2012) and Rhododendron delavayi (Duan et al, 2007) showed that the higher the temperature, the earlier seeds began to germinate (Zhang, 2012). There were significant difference among the effects of the three temperature regimes on germination percentage and vigor (Table 1).…”
Section: Effect Of Different Temperature On Germination Of Rhododendrmentioning
confidence: 97%
“…where ni is the number of seeds germinated at day i after sowing, di is the time between the beginning of the experiment and the end of a particular interval of measurement, and N is the total number of germinated seeds (Zhang, 2012). A modified Timson index of germination velocity = SG/t was used for estimating the GR, where ''G'' is germination percentage after every 48 h and ''t'' is the total germination period (20 d) (Hameed et al, 2014).…”
Section: Codementioning
confidence: 99%
“…The duration of the light period can influence germination depending on the required photoperiod of the species, as supported by studies from Araújo Neto et al (2003), Brown and Antos (2012), Oliveira and Innecco (2012), Varisco and Simonetti (2012), Zhang (2012) and Silva et al (2014a). According to TAKAKI (2001), all seeds have phytochrome, which controls the germination process.…”
Section: Introductionmentioning
confidence: 80%
“…Temperature affects the percentage and speed of germination, influencing water absorption by the seed and the metabolic biochemical reactions that regulate this process (CARVALHO; NAKAGAWA, 2012). Likewise, duration of the light period can influence germination, depending on the required photoperiod of the species (ARAÚJO NETO et al, 2003;BROWN;ANTOS, 2012;INNECCO, 2012;SILVA et al, 2014a;VARISCO;SIMONETTI, 2012;ZHANG, 2012). According to Influence of temperature and photoperiod on the germination of Senegalia bahiensis seeds Takaki (2001), all seeds have phytochrome, which controls the germination process, depending on how it is present in the seeds, as well as on the distinct responses to irradiation.…”
Section: Introductionmentioning
confidence: 99%